What Is Considered Development Economics? Commonalities and Differences in University Courses around the Developing World - McKenzie, David (Published by Oxford University Press on behalf of the World Bank, 2019)
We use a combination of surveys of instructors and data from course syllabi to examine how the subject of development economics is taught at the undergraduate and Master’s level in over 200 courses in 56 developing countries and the United States. We find there is considerable heterogeneity in what is considered development economics: there is a narrow core of topics (growth theory, poverty and inequality, human capital, and institutions) taught in at least half the classes and large variation in the role of theory versus empirics. Employing clustering techniques, we find four views of development: a theoretical macro-based approach; an empirical micro-based approach; a mixed approach narrowly focused on these common core topics; and an expansive approach covering a much broader range of topics. We find country, course, and instructor characteristics are all associated with these differences in how development economics is conceptualized.